Analysis of the Influence of Human Resource Development, Motivation, and Work Environment on Employee Performance and Employee Productivity (Case Study at PT. Mandiri Karya Kirana) - Pridynafiah, Levina; Waluyo, Minto (Program Pascasarjana Magister Teknik Industri Universitas Mercu Buana, 2024)
The success of a company is determined by the quality of its human resources, motivation, and work environment. One way to maintain quality and quantity is by enhancing and sustaining employee performance and productivity, thereby achieving the company's goals to the fullest. When employee performance and productivity are good, the objectives of a company, such as PT Mandiri Karya Kirana, in increasing profits, will be carried out effectively. Hence, this research seeks to understand the influence from human resource development, motivation, and work environment on employee performance and employee productivity at PT Mandiri Karya Kirana. The research methodology employed is the Structural Equation Modeling (SEM) method, with a sample size of 100 respondents. The results of research indicate that human resource development has a positive and significant impact on employee performance, motivation has a positive but non-significant impact on employee performance, the work environment could not be proven due to its exclusion from the research model, and employee performance has a positive and significant impact on employee productivity, obtaining a simultaneous equation Y2 = 0.528 X₁ + (0.085) X₂ + Z₄.